Persepsi siswa terhadap pembelajaran speaking bahasa inggris di Madrasah - Muzaky, Farel Ahmad (Maliki Interdisciplinary Journal, 2026)
English is essential for addressing global challenges, particularly speaking skills, which remain difficult for many madrasah students. This study aims to explore students’ perceptions of English speaking instruction in madrasahs and to identify factors that support and hinder the success of speaking learning. The research adopts a descriptive qualitative approach, focusing on students’ experiences, perspectives, and perceptions of the learning process they undergo. Data were collected through qualitative methods such as observation, interviews, and student reflections. The findings indicate that students’ perceptions significantly influence their engagement and confidence in speaking English. Positive perceptions encourage active participation, whereas negative perceptions lead to passive behavior and speaking anxiety. Communicative teaching methods and a supportive classroom environment serve as facilitating factors, while limited time, learning media, and conventional teaching methods act as barriers. This study highlights the importance of contextual and humanistic speaking instruction in madrasahs